2019
DOI: 10.1016/j.ultsonch.2019.104721
|View full text |Cite
|
Sign up to set email alerts
|

A novel rotation generator of hydrodynamic cavitation for the fibrillation of long conifer fibers in paper production

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
1
25
0
1
Order By: Relevance
“…After that, the applications of HC have begun to attract attention in a wide variety of areas, especially in the last few years (Figure 1). Nowadays, researchers have found that HC can be an effective tool for a number of chemical, biological, and other types of applications, e.g., microbial inactivation [bacteria (Mane et al, 2020), algae (Waghmare et al, 2019), virus (Kosel et al, 2017)], the removal of organic compounds (acids Choi et al, 2019, antibiotics (Tao et al, 2018, pesticides (Panda and Manickam, 2019), dyes Yi et al, 2018, pharmaceuticals (Rajoriya et al, 2019, fuel (Torabi Angaji and Ghiaee, 2015), phenols Chakinala et al, 2008, etc.,) decomposition of wasteactivated sludge (WAS) (Nabi et al, 2019), depolymerization (Prajapat and Gogate, 2019), denitrification (Song et al, 2019), desulfurization (Gagol et al, 2019), fibrillation (Kosel et al, 2019), intensification of biogas production (Zielinski et al, 2019), biofuel synthesis (Chipurici et al, 2019), liposome destruction (Pandur et al, 2020), catalyst slurry preparation (Nagalingam et al, 2019), viscosity reduction (Gregersen et al, 2019), residual stress relief, cleaning, and emulsification (Wu et al, 2019).…”
Section: Hydrodynamic Cavitationmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the applications of HC have begun to attract attention in a wide variety of areas, especially in the last few years (Figure 1). Nowadays, researchers have found that HC can be an effective tool for a number of chemical, biological, and other types of applications, e.g., microbial inactivation [bacteria (Mane et al, 2020), algae (Waghmare et al, 2019), virus (Kosel et al, 2017)], the removal of organic compounds (acids Choi et al, 2019, antibiotics (Tao et al, 2018, pesticides (Panda and Manickam, 2019), dyes Yi et al, 2018, pharmaceuticals (Rajoriya et al, 2019, fuel (Torabi Angaji and Ghiaee, 2015), phenols Chakinala et al, 2008, etc.,) decomposition of wasteactivated sludge (WAS) (Nabi et al, 2019), depolymerization (Prajapat and Gogate, 2019), denitrification (Song et al, 2019), desulfurization (Gagol et al, 2019), fibrillation (Kosel et al, 2019), intensification of biogas production (Zielinski et al, 2019), biofuel synthesis (Chipurici et al, 2019), liposome destruction (Pandur et al, 2020), catalyst slurry preparation (Nagalingam et al, 2019), viscosity reduction (Gregersen et al, 2019), residual stress relief, cleaning, and emulsification (Wu et al, 2019).…”
Section: Hydrodynamic Cavitationmentioning
confidence: 99%
“…The results from the corresponding research indicated the effectiveness of the treatment, economic efficiency which is far beyond those of traditional devices in the removal 2018and HCRs, (B) Venturi, and (C) rotor-stator type (Zupanc et al, 2014). of microorganism (Milly et al, 2007(Milly et al, , 2008Šarc et al, 2018;Sun et al, 2018a,b;Maršálek et al, 2020), WAS treatment (Petkovšek et al, 2015;Kim et al, 2019Kim et al, , 2020SeŽun et al, 2019), organic wastewater treatment (Badve et al, 2013;Zupanc et al, 2014), biofuel synthesis (Mohod et al, 2017;Chipurici et al, 2019), fibrillation (Kosel et al, 2019), intensification of biogas production (Patil et al, 2016), and delignification (Badve et al, 2014), etc., even without geometrical optimization or in scaled-up application. In addition, due to the extreme conditions and the hydroxyl radicals produced by HC, effective synergic effects between HC and heating, AC (Sun et al, 2018a), various oxidants (Saharan et al, 2011), photocatalyst (Wang et al, 2011), photolysis (Zupanc et al, 2014), and electrochemical (Wang et al, 2010) have been proved.…”
Section: Development Of Hcrmentioning
confidence: 99%
“…Recently, we have also investigated the application of cavitation in the paper production industry. We have shown that cavitation can be used to replace processes such as homogenization, fibrillation, and refining of paper pulp [36].…”
Section: Contributions Of Our Research Group On the Topic Of Hc Use Imentioning
confidence: 99%
“…Because HC is artificially generated by hydrodynamic cavitation reactors (HCRs), therefore, the design of high-performance HCRs is extremely vital for the effectiveness and economical efficiency of HC technology [23] . Unlike conventional HCRs (e.g., Venturi tubes or orifice plates) which have been widely utilized on a laboratory scale [24] , advanced rotational HCRs (ARHCRs) are found to yield significant effects in large numbers of scaled-up applications, such as water disinfection [25] , [26] , [27] , [28] , [29] , [30] , decomposition of waste-activated sludge (WAS) [31] , [32] , [33] , [34] , degradation of organic matter [35] , [36] , [37] , biofuel synthesis [38] , [39] , [40] , fibrillation [41] , intensification of biogas production [42] , and delignification [43] .…”
Section: Introductionmentioning
confidence: 99%
“…Though numerous application-based work has been published on ARHCRs, the amount and depth of the fundamental research on ARHCRs are still considerably limited [44] . Even though a number of researchers have investigated the cavitation flow in ARHCRs by experimental flow visualization [27] , [28] , [33] , [37] , [41] , [44] , [45] , [46] and computational fluid dynamics (CFD) [47] , their corresponding mechanisms, especially for interaction-type reactors (i.e., cavitation is generated by the interaction motion between the rotor and stator) [33] , [35] , [37] , [41] , [44] , [45] , are still not well understood. Specifically, no researcher has quantitatively analyzed the cavitation development process in accordance with the visualization results.…”
Section: Introductionmentioning
confidence: 99%